(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The purpose of this study is to explore the provision of information resources for enhancing the utilization and user satisfaction of school libraries among secondary school students in Katsina state. School libraries play a crucial role in supporting students’ educational and personal development by providing access to a wide range of information resources. However, there is a growing concern about the lack of utilization and user satisfaction. This research was carried to investigate the factors influencing the use of school libraries. The study employ a quantitative methods approach, to gather data from secondary school students. The quantitative method will involve administering surveys to representative sample of secondary school students to assess their awareness, attribute, and frequency of library use. Additionally, data will be collected on the availability and adequacy of information resources, including books, digital materials, and other references materials. The population of the study comprises of eight hundred students from eight secondary schools in Katsina Local government Area, one hundred questionnaires were administer and eighty were returned for data analysis. The findings of the study revealed that the kind of information resources available in secondary school of Katsina Local Government Area are textbooks, information resources are highly being utilized in secondary school of Katsina Local Government Area, The format of information resources available in secondary school of Katsina Local Government Area are mainly print materials, the extent to which teachers and students satisfied with available library resources in secondary school of Katsina Local Government Area are highly satisfied, the challenges facing the information resources available in secondary school of Katsina Local Government Area is inadequate funding and the ways in which the challenges are tackled is through provision of adequate funding. And the study recommend that government, private organizations and philanthropic should invest in school libraries. There should be provision of adequate budgetary allocation to school libraries to enhance effective library and information services among others.